Risk of thrombotic events and other complications in anticoagulant users infected with SARS-CoV-2: an observational cohort study in primary health care in SIDIAP (Catalonia, Spain) - Maria Giner-Soriano; Ainhoa Gomez-Lumbreras; Cristina Vedia; Dan Ouchi; Rosa Morros (BMC Primary Care, 2022)
Abstract Background The risk of thromboembolic events and COVID-19 complications in anticoagulated patients once hospitalized has been widely analyzed. We aim to assess these outcomes in primary health care (PHC) patients chronically treated with oral anticoagulants (OAC) in comparison with non-treated. Methods Cohort study including adults with COVID-19 diagnosis in the PHC records in Catalonia, Spain; from March to June 2020. Patients were matched between exposed and non-exposed to OAC based on age and gender in a 1:2 design. Data source is the Information System for Research in Primary Care (SIDIAP). Results We included 311,542 individuals with COVID-19. After propensity score matching, we obtained a cohort of 20,360 people, 10,180 exposed and 10,180 non-exposed to OAC. Their mean age was 79.9 and 52.1% were women. Patients exposed to OAC had a higher frequency of comorbidities than non-exposed. Anticoagulated patients had a higher risk of hospital admission (IRR 1.16, 95% CI 1.03–1.29), and of stroke and pulmonary embolism than non-anticoagulated (IRR 1,80, 95% CI 1.06–3.06). The risk of pneumonia was not different between groups (IRR 1.04, 95% CI 0.84–1.30). We found a lower risk of death in patients exposed to OAC (IRR 0.60, 95% CI 0.55–0.65). Conclusions OAC users in our study had more comorbidities and were older than non-users, well known risks for hospitalization being confirmed with our results. We also found in our study that OAC exposure was not associated to an increased risk in the mortality rate, and it was associated with higher risks of hospital admission and thromboembolic events, although we cannot assess the effect of the interventions applied during hospital admission on the outcomes studied, as our database is a PHC database. Trial registration EUPAS register: EUPAS37205 .